Association between Depression and Factors Affecting Career Choice among Jordanian Nursing Students - Yousef, Said; Athamneh, Mariam; Masuadi, Emad; Ahmad, Haitham; Loney, Tom; Moselhy, Hamdy F.; Al-Maskari, Fatma; ElBarazi, Iffat (Frontiers in Public Health, 2017)
Background Although stress reaction is high among nursing staff and nursing students in the Middle East and its effect on life is known, there are scant studies reporting on these clinical and social features. In addition, there are no studies reporting on factors that influence career choice among this group. Aim This study aimed to investigate factors that influence career choice among nursing students and their possible association with depressive symptoms. Method Participants were 150 (84.7% response rate) nursing students randomly selected from each academic year at the Nursing College/Jordan University of Science and Technology. Participants consented and completed the socio-demographic data collection sheet. The Arabic version of the Beck Depression Inventory-II Scale was used to assess participants with respect to depressive symptoms. A modified list of factors influencing career choice and a Likert scale to assess the level of sadness and the degree of religiosity were used as well. Results Students ranked the most important three factors influencing their career selection as family decision, religious factors, and the desire to care for others. The prevalence of depression among the sample was 26%. Students who had a desire to care for others were less likely to suffer from depression and those who chose nursing as their career due to religious factors were significantly less depressed than those who did not. Meanwhile, students who chose nursing under family pressure or because of a lack of alternative opportunities were more depressed. The odds ratio for depressive symptoms was 0.24 when students chose nursing because of religious factors, whereas it was 4.92 when the family strongly influenced the student’s career decision and 3.61 when a nursing career was the only perceived opportunity available. Conclusion The main factors associated with depression among this sample of nursing students were pressure from their family to choose a nursing career and having no other career or employment opportunities. Religiosity was negatively associated with depression and may act as a protective factor; however, future studies using longitudinal designs will need to confirm this hypothesis.